1984
DOI: 10.1099/00221287-130-4-803
|View full text |Cite
|
Sign up to set email alerts
|

The Microbial Ecology of Pilosebaceous Units Isolated from Human Skin

Abstract: A method allowing isolation and microbiological analysis of individual pilosebaceous units (follicles) was used to study biopsies of back skin obtained from volunteer acne vulgaris patients. The main microbial groups isolated were members of the genera Propionibacterium, Staphylococcus and Pityrosporum. The incidence (and mean density) of these organisms in 140 normal follicles was 12% (2.6 x lo5 per follicle), 4% (5.5 x lo3 per follicle) and 13% (lo2 per follicle) respectively. Colonized follicles were not di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
75
1
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 14 publications
4
75
1
1
Order By: Relevance
“…Folliculitis appears to be more common in tropical countries (1,199), probably due to the heat and humidity. Although Malassezia has frequently been isolated from folliculitis lesions (137,149,212,318), this may not be significant, since it can also be isolated from normal pilosebaceous follicles (243) and noninflamed open comedones in acne vulgaris (193). Other organisms commonly found in normal follicles include propionibacteria and staphylococci (243).…”
Section: Malassezia Folliculitismentioning
confidence: 99%
See 1 more Smart Citation
“…Folliculitis appears to be more common in tropical countries (1,199), probably due to the heat and humidity. Although Malassezia has frequently been isolated from folliculitis lesions (137,149,212,318), this may not be significant, since it can also be isolated from normal pilosebaceous follicles (243) and noninflamed open comedones in acne vulgaris (193). Other organisms commonly found in normal follicles include propionibacteria and staphylococci (243).…”
Section: Malassezia Folliculitismentioning
confidence: 99%
“…Although Malassezia has frequently been isolated from folliculitis lesions (137,149,212,318), this may not be significant, since it can also be isolated from normal pilosebaceous follicles (243) and noninflamed open comedones in acne vulgaris (193). Other organisms commonly found in normal follicles include propionibacteria and staphylococci (243). Few studies of Malassezia folliculitis have attempted to culture the follicular contents, but one that did also found propionibacteria and staphylococci present within affected follicles (212).…”
Section: Malassezia Folliculitismentioning
confidence: 99%
“…P. acnes colonizes the skin and follicles of both acne-affected and healthy individuals, and no correlation has been observed between the absolute number of bacteria and the severity of disease (8,9,23,25). It has even been reported that not all comedones or early inflamed lesions harbor microorganisms (23,24). In addition, beta-lactam antibiotics are ineffective against acne, although P. acnes is fully sensitive to these drugs (36).…”
mentioning
confidence: 99%
“…Microorganisms colonizing the skin not only reside on the skin surface but are also found to inhabit hair follicles and lower skin depths (8). Many antimicrobial agents exhibit restricted permeation of the skin (8) and fail to reach the deeper layers, including the hair follicles, which harbor coagulasenegative staphylococci (2,7,8,13,15) and propionibacteria (13). Commensal microorganisms may therefore persist at the site of incision following skin antisepsis (4, 22), and such resident organisms may cause infection when the protective skin barrier is breached during surgical procedures (12,20,26).…”
mentioning
confidence: 99%